Nature does not Create Unnecessary Things - Sikora, Agnieszka; Skubała, Piotr (No Limits, 2021)
Zero waste is an idea demanding a change in the way we think about and function in the environment. It points out that human activity should be connected with the responsibility for how we live and what consequences our actions have on the planet. The idea behind zero waste is to minimize the amount of waste and reuse it, as well as not to waste purchased products. Due to the fact that we use environmental resources, it is worth remembering that everything we buy and then use becomes waste. Therefore, the emphasis on changing our habits and lifestyles is so important, but what matters the most is to reduce excessive consumerism.